EVEKTIVITAS KERJASAMA INDONESIA DAN MALAYSIA DALAM PROGRAM HIDRILISASI KELAPA SAWIT PERIODE 2020-2021 - Anita, Anita (Universitas Islam Negeri Raden Intan Lampung, 2024)
ABSTRACTThe aim of this research is to determine the cooperation between Indonesia and Malaysia in palm oil hydrylization. This research uses the basic theory, namely hydrylization. This research This research is included in qualitative research. Quantitative research is research that uses numbers either directly taken from research results or data processed using statistical analysis. Data Source The data source used in this research is secondary data. Secondary data is research data obtained by researchers indirectly through intermediary media (data obtained and recorded by other parties). Secondary data can generally be in the form of evidence, historical notes or reports that have been compiled in archives (documentary data), both published and unpublished. The instruments for this research are two countries, namely Indonesia and Malaysia. These two countries are the two main producers of palm oil in the world and have an important role in the global palm oil industry.Keywords : Cooperation, Downstreaming, Palm Oil